2016
DOI: 10.1002/cphc.201600241
|View full text |Cite
|
Sign up to set email alerts
|

Specific Anion Effects on the Kinetics of Iodination of Acetone

Abstract: Specific ion effects on the kinetics of iodination of acetone in an acidic medium are investigated by UV/Vis spectrophotometry as a function of nature of the acid and temperature. The results indicate that the order of the reaction with respect to acetone is practically unaffected by the composition of the acid while the value of the mixed constant k1 K increases according to the sequence HBr Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In this study reactants acetone (Ac) and iodine (I2) are combined with hydrochloric acid (HCl) catalyst to produce iodoacetone. [23] Students analyze the effect of varying reactant concentration and reaction temperature on the reaction rate. The reaction mechanism for the iodination of acetone is represented by three elementary steps, as shown in Equations (3)(4)(5).…”
Section: ○ Figure 3 Kin Experimental Apparatus: One-liter Jacketed Gl...mentioning
confidence: 99%
“…In this study reactants acetone (Ac) and iodine (I2) are combined with hydrochloric acid (HCl) catalyst to produce iodoacetone. [23] Students analyze the effect of varying reactant concentration and reaction temperature on the reaction rate. The reaction mechanism for the iodination of acetone is represented by three elementary steps, as shown in Equations (3)(4)(5).…”
Section: ○ Figure 3 Kin Experimental Apparatus: One-liter Jacketed Gl...mentioning
confidence: 99%
“…Such a mechanistic scenario has been found, for example, for the iodination of acetone, where the tautomerization to the enol of acetone is rate-determining and the overall rate is independent of iodine and acetone concentrations. 119,120 As the initial oxidation of 4a and 4b to the ferrocenium ions [4a] •+ and [4b] •+ is very fast (vide supra), these ferrocenium cations [4a] •+ and [4b] •+ are likely involved in the preequilibrium. Furthermore, we suggest that the counterions X − of the oxidant plays a role for [4a] •+ as the very weakly coordinating anion [Al{OC(CF 3 ) 3 } 4 ] − does not support the formation of the EPR-active species 4a-X, while [SbCl 6 ] − , [PF 6 ] − , or [NO 3 ] − do.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Investigations of SIE over the past 100 years have focused on aqueous solutions despite their broader occurrence in nonaqueous solvents. Mazzini and Craig systematically examined SIEs in nonaqueous solvents and found that they were universally observed and that a similar series is followed in all solvents at infinite dilution, demonstrating that SIEs are fundamentally a property of the ion, rather than the solvent. However, ion specificity is perturbed by the type of solvent at finite concentrations, hence, the behavior of ions in various solvents must be systematically investigated in order to understand how the solvent impacts the observed SIE.…”
Section: Introductionmentioning
confidence: 99%